Correlation of Leukocytes, Neutrophil-To-Lymphocyte Ratio, C-Reactive Protein, and Serum Lactate with Amputation Incidence in Diabetic Foot Ulcer Patients - Primadian, Krisandi; Hapsari, Putie; Yarman, Indra Prasetya; Soedjana, Hardisiswo; Djajakusumah, Teguh Marfen (Majalah Kedokteran Bandung, 2025)
Diabetic foot ulcers are a major cause of approximately 85% of amputations in non-trauma patients. One of the contributing factors is the presence of extensive gangrenous infections. Effective management of diabetic foot infections to prevent amputation requires knowledge of various factors such as ulcer location, depth, neuropathy, vasculopathy, infection, and the presence of infection, which can be identified through inflammatory markers. This retrospective cohort study aimed to evaluate the correlation between leukocyte count, neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP), and serum lactate levels with the incidence of amputation in DFU patients. All DFU patients admitted to Dr. Hasan Sadikin General Hospital, Bandung, from January 1 to December 31, 2023, who met the inclusion criteria were included using purposive sampling. A total of 47 patients with diabetic foot ulcers were included in this study. The mean, median, and range of leukocytes were 18,532, 16,015, and 55,184, respectively, with higher values observed in amputation cases. NLR values were also higher in amputation cases, with a mean of 9.54, median of 6.00, and range of 47.32. Similarly, CRP levels were elevated in amputation cases, with a mean of 9.56, median of 6.75, and range of 26.16. There is a significant correlation between leukocytes, NLR, CRP, and serum lactate with the incidence of amputation in diabetic foot ulcer patients.